2021
DOI: 10.1186/s12888-021-03056-x
|View full text |Cite
|
Sign up to set email alerts
|

Surgical experience for patients with serious mental illness: a qualitative study

Abstract: Background People with serious mental illness (SMI) have significantly worse surgical outcomes compared to the general population. There are many contributing factors to this complex issue, however consideration of the surgical experience from the patient’s own perspective has never been undertaken. This lack of understanding prevents the provision of truly patient centred care and may limit the impact of potential improvement initiatives. Therefore this study aims to describe and better unders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…In contrast, several psychiatrists indicated that due to the known mistrust of the health system and fear of stigmatization, patients with SMI will not respond truthfully to the tool no matter what is included, resulting in false negatives. Whilst these challenges are well known [ 25 ] and important to highlight, none of the mental health consumers in this study reported being unwilling to use the tool, which is in line with the feedback previously highlighted regarding surgical patients with SMI wanting to have their mental health acknowledged [ 9 ]. The brevity and accuracy of the K10 has also been demonstrated as being a suitable tool for screening SMI in the general population [ 26 ].…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In contrast, several psychiatrists indicated that due to the known mistrust of the health system and fear of stigmatization, patients with SMI will not respond truthfully to the tool no matter what is included, resulting in false negatives. Whilst these challenges are well known [ 25 ] and important to highlight, none of the mental health consumers in this study reported being unwilling to use the tool, which is in line with the feedback previously highlighted regarding surgical patients with SMI wanting to have their mental health acknowledged [ 9 ]. The brevity and accuracy of the K10 has also been demonstrated as being a suitable tool for screening SMI in the general population [ 26 ].…”
Section: Discussionsupporting
confidence: 79%
“…Although limited, there is evidence to show that even modest preoperative psychological interventions can have favourable effects on surgical patient outcomes by matching a range of interventions to the needs of the patients [ 8 ]. In addition, and perhaps most critically, patients with SMI have described their support and desire for having the status of their mental health acknowledged prior to surgery and identified screening as a potential solution [ 9 ]. Currently there are no known mental health screening tools designed specifically for use in the routine surgical setting that cover a broad range of psychological conditions and symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Surgeons are more likely to overlook comorbid psychiatric disorders than physical comorbidities. They infrequently ask about patients’ mental health and report low confidence in caring for patients with mental health issues [ 20 ]. Educational initiatives must be undertaken to enlighten surgeons on the unique needs of this disadvantaged population to improve surgical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19][20][21][22][23] Systemrelated factors result in the healthcare system systematically failing to prevent, identify and treat physical diseases. 12,24,25 Also, health professionals, including surgeons and emergency care professionals, still demonstrate stigmatising behaviours towards patients with severe mental illness [26][27][28][29] which may explain some of the described variation.…”
Section: From Lack Of Engagement To Engagement Of All Stake Holdersmentioning
confidence: 99%
“…21,22,116,126,129,[131][132][133] For patients with mental health, stigma may be a particular problem. 26,27,134 . Likewise, diagnostic overshadowing, i.e., 'assuming that a symptom is due to co-existing mental health conditions rather than exploring the cause of the patient's symptoms' is being reported for this patient groups.…”
Section: Public Health Social Position and Equity In Carementioning
confidence: 99%